Studi Minat Penggunaan Bank Digital oleh Mahasiswa Fakultas Teknik Universitas Diponegoro - Kevin Richardo Runtu; Rahaditya Agung Prakosa; Muhammad Rais Pratama (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The rapid pace of innovation in technology has overhauled the banking world, giving rise to digital banks that provide convenience and efficiency. However, how much students, especially those studying in engineering and exposed to technology, adopt digital banks still needs to be studied in depth. This study aims to evaluate the interest of students at the Faculty of Engineering, Diponegoro University regarding the use of digital banks. The method utilized in this research is a quantitative approach, by distributing questionnaires to 250 students of the Faculty of Engineering, Diponegoro University. The variables studied include perceptions of ease of use, perceived benefits, level of trust, and influence from the social environment. The results showed that perceptions of ease of use and perceived usefulness had a significant positive impact on interest in using digital banks. In contrast, the level of trust and influence from the social environment did not show a significant impact. From the findings of this study, it is desirable to provide advice for those who provide digital bank services to develop more effective marketing strategies for students, emphasizing the convenience aspects and direct benefits offered by the service.